PERLINDUNGAN KONSUMEN DALAM TRANSAKSI ELEKTRONIK - Rizka Syafriana (DE LEGA LATA: JURNAL ILMU HUKUM, 2016)
Consumer protection is a matter of human interest, therefore, a hope for all nations in the world to be able to make it happen. In Indonesia obstacles that hinder the development of trade via the Internet is in inadequate facilities that are needed for electronic dispute resolution institutions to cope.